Physical constitution matters for athletic performance and salary of NBA players - Linn-Brit Bakkenbüll (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2017)
Basketball is one of the most practised sports in the world, especially in America. America has the most famous professional basketball league, the National Basketball Association (NBA). This study examines whether there is a relationship between the physical constitution of professional basketball players and their athletic performance in the 2015/16 NBA season. Regression results show that the relative wingspan influences the athletic performance in a significantly positive way whereas the vertical jumping ability influences it in a significantly negative way. Furthermore, age follows an inverted U-shape with a maximum at 28 years. Moreover, this study analyses the impact of on-court performance measurements and personal characteristics on salary for NBA players. Taller players have a higher salary in the 2015/16 NBA season. – – Basketball ist eine der am meisten praktizierten Sportarten der Welt, insbesondere in den USA. Die USA haben die berühmteste professionelle Basketballliga, die National Basketball Association (NBA). Diese Studie untersucht, ob es einen Zusammenhang gibt zwischen der physischen Konstitution von professionellen Basketballspieler und ihrer sportlichen Leistung in der Saison 2015/16 der NBA. Regressionsergebnisse zeigen, dass die relative Armspannweite die sportliche Leistung in signifikant positiver Weise beeinfusst, während die vertikale Sprungfähigkeit einen signifikant negativen Einfluss ausübt. Außerdem hat das Alter einen invers U-förmigen Effekt mit einem Maximum bei 28 Jahren.Weiterhin untersucht diese Studie den Einfluss von Leistungsmaßen im Spiel und persönlichen Eigenschaften auf das Gehalt von NBA Spielern. Größere Spieler haben ein höheres Gehalt in der NBA-Saison 2015/16.
Keywords: J24; J31; J49; J71; M12; Z22; 650; Baseball; Sportler; Biologische Daten; Arbeitsleistung; Einkommenseffekt; USA